2021
DOI: 10.1074/jbc.ra120.016617
|View full text |Cite
|
Sign up to set email alerts
|

Conformational dynamics during high-fidelity DNA replication and translocation defined using a DNA polymerase with a fluorescent artificial amino acid

Abstract: We address the role of enzyme conformational dynamics in specificity for a high-fidelity DNA polymerase responsible for genome replication. We present the complete characterization of the conformational dynamics during the correct nucleotide incorporation forward and reverse reactions using stopped-flow and rapid-quench methods with a T7 DNA polymerase variant containing a fluorescent unnatural amino acid, (7-hydroxy-4-coumarin-yl) ethylglycine, which provides a signal for enzyme conformational changes. We sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(38 citation statements)
references
References 41 publications
5
33
0
Order By: Relevance
“…This study completes our prior characterization of the role of enzyme conformational dynamics in DNA polymerase nucleotide specificity (12,13,31,42) by extending our analysis of a high fidelity DNA polymerase to include the kinetics of misincorporation. Prior analysis of nucleotide-induced conformational changes using the T7 DNA polymerase E514Cou variant showed that for a correct base pair, the transition from the open to closed enzyme state was at least 20-fold faster than chemistry, but the reverse conformational change to allow release of the nucleotide was much slower than chemistry.…”
Section: Discussionsupporting
confidence: 65%
See 4 more Smart Citations
“…This study completes our prior characterization of the role of enzyme conformational dynamics in DNA polymerase nucleotide specificity (12,13,31,42) by extending our analysis of a high fidelity DNA polymerase to include the kinetics of misincorporation. Prior analysis of nucleotide-induced conformational changes using the T7 DNA polymerase E514Cou variant showed that for a correct base pair, the transition from the open to closed enzyme state was at least 20-fold faster than chemistry, but the reverse conformational change to allow release of the nucleotide was much slower than chemistry.…”
Section: Discussionsupporting
confidence: 65%
“…While k cat / K m values for a correct- and a mismatched-nucleotide incorporation have been reported (9,2931,33,34), general questions about misincorporation still remain, especially for high fidelity DNA polymerases. Are certain mismatches incorporated more efficiently than others?…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations